Antiphospholipid Syndrome and Vaccines (2014)
Antiphospholipid syndrome (APS) is an autoimmune multisystemic disease associated with recurrent fetal loss, thromboembolic phenomena, thrombocytopenia, and neurological, cardiac, and dermatological involvement. APS is characterized by the presence of antiphospholipid antibodies, which bind negatively charged phospholipids, mainly through ?2-glycoprotein I (?2GPI). Tetanus toxoid (TTd) is a potent exotoxin produced by the bacterium Clostridium tetani. DNA hepatitis B virus (HBV) vaccination was given to 85 healthy students and, 1 month post-vaccination, a minority of individuals showed changes in IgG or IgM anticardiolipin and anti-?2GPI antibodies or lupus anticoagulant. Toplak et al. reported the presence of anti-?2GPI antibodies in 15% of 92 healthy medical workers up to 6 months post-influenza vaccination. Molecular mimicry has been proposed as one of the mechanisms by which experimental APS can occur in association with pathogens. © 2015 Wiley-Blackwell.